Lability of prenatal stress during the COVID‐19 pandemic links to negative affect in infancy. (7th September 2022) - MacNeill, Leigha A.; Krogh‐Jespersen, Sheila; Zhang, Yudong; Giase, Gina; Edwards, Renee; Petitclerc, Amélie; Mithal, Leena B.; Mestan, Karen; Grobman, William A.; Norton, Elizabeth S.; Alshurafa, Nabil; Moskowitz, Judith T.; et al.
Abstract: The association between prenatal stress and children's socioemotional development is well established. The COVID‐19 pandemic has been a particularly stressful period, which may impact the gestational environment. However, most studies to‐date have examined prenatal stress at a single time point, potentially masking the natural variation in stress that occurs over time, especially during a time as uncertain as the pandemic. This study leveraged dense ecological momentary assessments from a prenatal randomized control trial to examine patterns of prenatal stress over a 14‐week period (up to four assessments/day) in a U.S. sample of 72 mothers and infants. We first examined whether varied features of stress exposure (lability, mean, and baseline stress) differed depending on whether mothers reported on their stress before or during the pandemic. We next examined which features of stress were associated with 3‐month‐old infants' negative affect. We did not find differences in stress patterns before and during the pandemic. However, greater stress lability, accounting for baseline and mean stress, was associated with higher infant negative affect. These findings suggest that pathways from prenatal stress exposure to infant socioemotional development are complex, and close attention to stress patterns over time will be important for explicating these pathways.